2013
DOI: 10.1093/hmg/ddt071
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenic Q555X SYN1 mutant triggers imbalances in release dynamics and short-term plasticity

Abstract: Synapsin I (SynI) is a synaptic vesicle (SV) phosphoprotein playing multiple roles in synaptic transmission and plasticity by differentially affecting crucial steps of SV trafficking in excitatory and inhibitory synapses. SynI knockout (KO) mice are epileptic, and nonsense and missense mutations in the human SYN1 gene have a causal role in idiopathic epilepsy and autism. To get insights into the mechanisms of epileptogenesis linked to SYN1 mutations, we analyzed the effects of the recently identified Q555X mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 51 publications
2
48
0
Order By: Relevance
“…The importance of characterizing the excitable phenotype developed by Syn deficiencies is highlighted by the fact that Syn deletion and mutations have been associated with the development of epileptic phenotypes in animals (Li et al, 1995;Rosahl et al, 1995;Gitler et al, 2004;Etholm and Heggelund, 2009;Ketzef et al, 2011;Etholm et al, 2013;Ketzef and Gitler, 2014). In humans, epilepsy and other disorders have been linked to mutations in SynI (Garcia et al, 2004;Fassio et al, 2011b;Lignani et al, 2013;Giannandrea et al, 2013) and SynII genes (Cavalleri et al, 2007;Lakhan et al, 2010;Corradi et al, 2014). In addition, the seizure susceptibility of mice TKO brain slices has been reported to anticipate epileptic phenotypes (Boido et al, 2010;Feliciano et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of characterizing the excitable phenotype developed by Syn deficiencies is highlighted by the fact that Syn deletion and mutations have been associated with the development of epileptic phenotypes in animals (Li et al, 1995;Rosahl et al, 1995;Gitler et al, 2004;Etholm and Heggelund, 2009;Ketzef et al, 2011;Etholm et al, 2013;Ketzef and Gitler, 2014). In humans, epilepsy and other disorders have been linked to mutations in SynI (Garcia et al, 2004;Fassio et al, 2011b;Lignani et al, 2013;Giannandrea et al, 2013) and SynII genes (Cavalleri et al, 2007;Lakhan et al, 2010;Corradi et al, 2014). In addition, the seizure susceptibility of mice TKO brain slices has been reported to anticipate epileptic phenotypes (Boido et al, 2010;Feliciano et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that Syn deficiency reduces GABAergic transmission and not affects or increases glutamatergic transmission, thus leading to a positive imbalance towards hyperexcitability (Terada et al, 1999;Gitler et al, 2004;Baldelli et al, 2007;Chiappalone et al, 2009;Ketzef et al, 2011;Farisello et al, 2012;Lignani et al, 2013;Feliciano et al, 2013;Medrihan et al, 2013;Medrihan et al, 2014 Klee, 1976 andAltrup, 2004). Finally, a key advantage of this monosynaptic cell model is that the presynaptic and postsynaptic compartments can be selectively targeted by injections and specific networks can be constructed by directly plating individual neurons on MEA electrodes.…”
Section: +mentioning
confidence: 99%
“…In addition, epidemiological studies reported several Syn mutations associated with several disorders, such as epilepsy in humans (García et al, 2004;Cavalleri et al, 2007;Lakhan et al, 2010;Fassio et al, 2011b;Lignani et al, 2013;Corradi et al, 2014).…”
Section: Increased Cellular Excitability In Syn Silenced Cellsmentioning
confidence: 99%
“…In mammals it has been shown that almost all single, double or triple Syn knock-out (KO) mice develop a severe epileptic phenotype induced by sensory stimulation (for review see Cesca et al, 2010 andFassio et al, 2011a). In humans, several nonsense and missense Syn mutations associated with epilepsy, among other disorders, have been reported and characterized to some degree, for both SYN1 (García et al, 2004;Fassio et al, 2011b;Lignani et al, 2013, Giannandrea et al, 2013 and SYN2 genes (Cavalleri et al, 2007;Lakhan et al, 2010;Corradi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation